Purification and characterization of an extracellular cold‐adapted alkaline lipase produced by psychrotrophic bacterium Yersinia enterocolitica strain KM1. (10th February 2015) - Ji, Xiuling; Chen, Guiyuan; Zhang, Qi; Lin, Lianbing; Wei, Yunlin
<x xml:space="preserve">Abstract</x> An extracellular cold‐adapted alkaline lipase from the psychrotrophic Yersinia enterocolitica strain KM1 was purified 26‐fold to homogeneity. The enzyme was active over a broad range spanning 0–60 °C with an optimum activity at 37 °C, and it was found to be alkaline‐preferring with an optimum activity at pH 9.0. The molecular weight was estimated to be 34.3 KDa and monomeric. The lipase could be activated by Ca2+ and low concentration (10%) of ethanol, dimethyl sulphoxide, methanol, and acetonitrile, whereas it was strongly inhibited by Zn2+, Cu2+, SDS, EDTA, and PMSF. Using p‐nitrophenyl butyrate as a substrate at 37 °C, the Km and Vmax of the enzyme were found to be 16.58 mM and 5.24 × 105 μM · min−1, respectively. This extracellular cold‐adapted alkaline lipase may be a good candidate for detergents and biocatalysts at low temperature.